DIRECT AND SIMULTANEOUS QUANTIFICATION OF ATORVASTATIN AND AMLODIPINE IN TABLETS BY NIR SPECTROSCOPY - VONICA-GLIGOR, Andreea Loredana; CASIAN, Tibor; REZNEK, Andra; TOMUȚĂ, Ioan; GLIGOR, Felicia (Studia Universitatis Babeș-Bolyai Chemia, 2015)
Near infrared spectroscopy (NIRS) is a technique widely used for direct and non-destructive analysis of solid samples. A NIRS method for the simultaneous quantification of atorvastatin and amlodipine in fixed-dose combination tablets was developed and fully validated. The PLS calibration model was developed based on the 26 samples prepared according to a D-optimal experimental design with 2 factors and 5 levels. The best predictive model for atorvastatin was developed using standard normal variate pre-processing method, 7 PLS factors; the best predictive model for amlodipine was developed using first derivate followed by standard normal variate pre-processing method and 7 PLS factors. The method was validated in terms of linearity, trueness, precision, and accuracy. The validation results show that the method is reproducible, precise and has good accuracy and linearity profiles. Furthermore, comparative data obtained on independent samples shows no statistical difference (p>0.05) between the results predicted by the NIRS method and the values obtained using HPLC reference method. So, NIRS based on PLS multivariate calibration could be a suitable tool for the non-destructive, direct and simultaneous prediction of the chemical composition of a fixed-dose combination that includes two APIs in a single tablet and is helpful in achieving the goals of Process Analytical Technology (PAT).